2003
DOI: 10.1253/circj.67.379
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Myocardial Angiotensin-Converting Enzyme Activity on Coronary Vascular Resistance and Serum Brain Natriuretic Peptide Concentration in Coronary Bypass Surgery

Abstract: Angiotensin-converting enzyme (ACE) inhibitors have cardioprotective effects in animals, but whether that occurs in humans is still controversial. The effect of myocardial ACE activity on coronary vascular resistance during coronary artery bypass surgery and on serum brain natriuretic peptide (BNP) concentration after surgery was studied in myocardial tissue sampled from the right atrium of patients during cardiac surgery (n=20). Tissue enzyme activity (nmol/min per mg protein) was measured using a photometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…2) after the surgery in spite of satisfactory post-operative course. Although clinical meaning of high level BNP is unclear at this moment [56,58], ACE inhibitor, quinapril, suppressed post operative atrial arrhythmia that occur until discharge of patients [4]. Supporting result of my study, recent large clinical study showed that ACE inhibitor plays a critical role in prevention of atrial fibrillation after the heart operation [59].…”
Section: Clinical Application Of Ace Inhibitor Against Ischmia/reperfmentioning
confidence: 61%
See 4 more Smart Citations
“…2) after the surgery in spite of satisfactory post-operative course. Although clinical meaning of high level BNP is unclear at this moment [56,58], ACE inhibitor, quinapril, suppressed post operative atrial arrhythmia that occur until discharge of patients [4]. Supporting result of my study, recent large clinical study showed that ACE inhibitor plays a critical role in prevention of atrial fibrillation after the heart operation [59].…”
Section: Clinical Application Of Ace Inhibitor Against Ischmia/reperfmentioning
confidence: 61%
“…Protective effects of ACE inhibitor against ischemia/reperfusion have been confirmed in left ventricular (LV) function, arrhythmia, and coronary circulation [1,4,[8][9][10][11]. ACE and kininase II are the same enzyme, and ACE inhibitors inhibit not only the generation of angiotensin II but also the degradation of several peptides, including bradykinin [12, 13].…”
Section: Effects Of Ace Inhibitor On Ischemia/reperfusion Injurymentioning
confidence: 99%
See 3 more Smart Citations